K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 12 2017

(2x2 - y)3 - 64y3 = (2x2 - y - 4y) [ (2x2 - y)2 + (2x2 - y).4y + 16y2 ] 

= (2x2 - 5y) (4x2 - 4x2y + y2 + 8x2y - 4y2 + 16y2)

= (2x2 - 5y) (4x2 + 4x2y + 13y2)

15 tháng 12 2017

(2x2-y)3-64y3=(2x2-y-4y)(2x2-y+4y)

                  =(2x2-5y)(2x2+3y)

23 tháng 10 2020

hjhjhjhhjhjhhhhjj

23 tháng 10 2020

( 2x2 - y )3 - 64y3

= ( 2x2 - y )3 - ( 4y )3

= ( 2x2 - y - 4y )[ ( 2x2 - y )2 + ( 2x2 - y ).4y + ( 4y )2 ]

= ( 2x2 - 5y )( 4x4 - 4x2y + y2 + 8x2y - 4y2 + 16y2 )

= ( 2x2 - 5y )( 4x4 + 4x2y + 13y2 )

Bài 1: 

\(=\dfrac{\left(\dfrac{1}{4}y-x\right)\left(\dfrac{1}{16}y^2+\dfrac{1}{4}xy+x^2\right)}{\dfrac{1}{4}y-x}=\dfrac{1}{16}y^2+\dfrac{1}{4}xy+x^2\)

Câu 2: 

\(\Leftrightarrow x-3+\left(2x+1\right)^2=20\)

\(\Leftrightarrow4x^2+4x+1+x-3=20\)

\(\Leftrightarrow4x^2+5x+2-20=0\)

=>4x^2+5x-18=0

hay \(x\in\left\{\dfrac{-5+\sqrt{313}}{8};\dfrac{-5-\sqrt{313}}{8}\right\}\)

23 tháng 8 2020

a) 9 + 10ab - a2 - 25b2 = 9 - (a2 - 10ab + 25b2)

= 9 - (a - 5b)2

= (3 - a + 5b)(3 + a - 5b)

b) 16x2 - (x2 - 2x + 1) = 16x2 - (x - 1)2

= (4x - x + 1)(4x + x - 1)

= (3x + 1)(5x - 1)

d) 12xy2 + 27y2 - 3y3 - 12x2 = 3(4xy2 + 9y2 - y3 - 4x2)

f) x4 + 64y4 = x4 + 16x2y2 + 64y4 - 16x2y2

= (x2 + 8y2)2 - 16x2y2

= (x2 - 4xy + 8y2)(x2 + 4xy + 8y2)

16 tháng 8 2015

a/ \(=64y^4+32xy^3+8y^2x^2-32xy^3-16x^2y^2-4x^3y+8x^2y^2+4x^3y+x^4\)

\(=8y^2\left(8y^2+4xy+x^2\right)-4xy\left(8y^2+4xy+x^2\right)+x^2\left(8y^2+4xy+x^2\right)\)

\(=\left(8y^2-4xy+x^2\right)\left(8y^2+4xy+x^2\right)\)

b/ \(=y^4+2xy^3+2x^2y^2-2xy^3-4x^2y^2-4x^3y+2x^2y^2+4x^3y+4x^4\)

\(=y^2\left(y^2+2xy+2x^2\right)-2xy\left(y^2+2xy+2x^2\right)+2x^2\left(y^2+2xy+2x^2\right)\)

\(=\left(y^2-2xy+2x^2\right)\left(y^2+2xy+2x^2\right)\)

c/ \(=x^4+5x^3+7x^2+5x^3+25x^2+35x+3x^2+15x+21\)

\(=x^2\left(x^2+5x+7\right)+5x\left(x^2+5x+7\right)+3\left(x^2+5x+7\right)\)

\(=\left(x^2+5x+3\right)\left(x^2+5x+7\right)\)

d/ \(=x^4+x^3+x^2-x^3-x^2-x+x^2+x+1\)

\(=x^2\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2-x+1\right)\left(x^2+x+1\right)\)

25 tháng 9 2018

1 ) x3 - 2x2 + x

= x( x2 - 2x + 1 )

= x ( x-1)2

2) 4x3 - 25x 

= x ( 4x2 - 25)

= x( 2x-5) ( 2x +5)

25 tháng 9 2018

11)  \(x^2-y^2-4x+4\)

\(=\left(x^2-4x+4\right)-y^2\)

\(=\left(x-2\right)^2-y^2\)

\(=\left(x-y-2\right)\left(x+y-2\right)\)

13)  \(x^4+4=x^4+4x^2+4-4x^2\)

\(=\left(x^2+2\right)^2-4x^2\)

\(=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)

1: \(=\left(x-1\right)\left(3x+7x^2\cdot2\right)=\left(x-1\right)\cdot x\cdot\left(3+14x\right)\)

2: \(=\left(x-y\right)\left(x^2+1\right)\)

3: \(=4x\cdot\left(x-2y\right)-8y\left(x-2y\right)\)

\(=4\left(x-2y\right)\left(x-2y\right)=4\left(x-2y\right)^2\)

5: \(=x^2\left(25-\dfrac{1}{81}y^2\right)=x^2\left(5-\dfrac{1}{9}y\right)\left(5+\dfrac{1}{9}y\right)\)